Exploratory study on family influence on current smoking habit among secondary school children in Kuching, Sarawak: case study SMK Sg. Tapang / Ismadi Nahar ... [et al.] - Nahar, Ismadi; Salang, Genevieve Kumang; Charlie, Jacqueline; Kepli, Roziah (2007)
Smoking, a well -known health risk, is increasingly acquired at younger ages, during late childhood and adolescence. Cigarette manufacturers are known to target young children with their aggressive advertising but they could well be helped unwittingly by adult members of hundreds of thousands of families to promote their deadly products. Many studies have shown significant association between smoking habits of family members especially that of the father's smoking habit on student's smoking habit. The behaviors are imitated more often when models are of the same sex, well respected, receive tangible rewards for their actions and are perceived as similar to the observers. Thus family especially parental behaviors strongly influence children's and adolescents' behaviors both positively and negatively.